Measurable benefits on brain activity from the practice of educational leisure - Requena, Carmen (Frontiers in Aging Neuroscience, 2014)
Even if behavioural studies relate leisure practices to the preservation of memory in old persons, there is unsubstantial evidence of the import of leisure on brain activity. Aim of this study was to compare the brain activity of elderly retired people who engage in different types of leisure activities. Methods: quasi-experimental study over a sample of 60 elderly, retired subjects distributed into three groups according to the leisure activities they practised: educational leisure (G1), memory games (G2) and card games (G3). Applied measures include the conceptual distinction between free time and leisure, the Test of Organization of Free Time (TOFT) measuring 24 clock divisions, and EEG register during 12 word list memorizing. The results show that the type of leisure activity is associated with significant quantitative differences regarding the use of free time. G1 devotes more time to leisure activities than G2 (p = 0.007) and G3 (p = 0.034). G1 rests more actively than the other two groups (p=0.001). The electrical localization of brain activity indicated a reverse tendency of activation according to the bands and groups. Discussion. Engaging in educational leisure activities is a useful practice to protect healthy brain compensation strategies. Future longitudinal research may verify the causal relation between practicing educational leisure activities and functional brain aging.